High, but stable, trend in the prevalence of gestational diabetes mellitus: A population‐based study in Xiamen, China. Issue 5 (11th April 2019) - Yan, Bing; Yu, Yaxin; Lin, Mingzhu; Li, Zhibin; Wang, Liying; Huang, Peiying; Song, Haiqu; Shi, Xiulin; Yang, Shuyu; Li, Xiaoying; Li, Xuejun
Abstract: Aims/Introduction: Diabetes prevalence in China has increased, but the trend in gestational diabetes mellitus prevalence is unclear. The objective of the present study was to examine the prevalence of gestational diabetes in Xiamen, China, and its association with maternal risk factors. Materials and Methods: This linked‐database cohort study used the Medical Birth Registry of Xiamen. Between 1 March 2011 and 30 March 2018, 78, 572 women who were diagnosed with gestational diabetes mellitus (GDM) were enrolled in the study. Maternal factors associated with the prevalence of GDM were examined using multivariate logistic regression. Results: A total of 13, 738 (17.6%) pregnant women were diagnosed with GDM according to the International Association of Diabetes and Pregnancy Study Groups criteria. GDM prevalence ranged from 15.5% (2012) to 19.9% (2017). Increasing age was associated with GDM; women aged >40 years versus those aged >25 years had an adjusted odds ratio (OR) of 5.91 (95% confidence interval [CI] 4.202–8.314). A positive correlation was observed between weight and GDM risk; obese women versus normal‐weight women had an adjusted OR of 2.508 (95% CI 2.253–2.792). Family history of diabetes and hypertension were more commonly observed among women with GDM. Multivariate analysis showed that family history of diabetes (OR 1.101, 90% CI 1.028–1.180), weight gain during early pregnancy (OR 1.087, 90% CI 1.052–1.124) and systolic blood pressure (OR 1.015, 90% CI 1.011–1.020) were risk factors associated with GDM incidence. Conclusions: GDM affects 17.6% of all pregnant women in Xiamen. Age and maternal obesity were major contributors to GDM. The trend of GDM risk remained stable during the study. Abstract : The objective of this study was to examine recent trends in the prevalence of gestational diabetes mellitus (GDM) in Xiamen, China, and to investigate its associations with maternal risk factors. Overall, in this study, GDM affected 17.6% of all pregnant women in Xiamen, China. Maternal age and obesity were major contributors to GDM. Encouragingly, the trend of GDM risk remained stable over the course of the study.